Overexpression of MUC1 Induces Non-Canonical TGF-β Signaling in Pancreatic Ductal Adenocarcinoma - Bose, Mukulika; Grover, Priyanka; Sanders, Alexa J.; Zhou, Ru; Ahmad, Mohammad; Shwartz, Sophia; Lala, Priyanka; Nath, Sritama; Yazdanifar, Mahboubeh; Brouwer, Cory; Mukherjee, Pinku (Frontiers in Cell and Developmental Biology, 2022)
Pancreatic ductal adenocarcinoma (PDA) is one of the most lethal human cancers. Transforming Growth Factor Beta (TGF-β) is a cytokine that switches from a tumor-suppressor at early stages to a tumor promoter in the late stages of tumor development, by yet unknown mechanisms. Tumor associated MUC1 is aberrantly glycosylated and overexpressed in >80% of PDAs and is associated with poor prognosis. MUC1 expression is found in the early stages of PDA development with subsequent increase in later stages. Analysis of human PDA samples from TCGA database showed significant differences in gene expression and survival profiles between low and high MUC1 samples. Further, high MUC1 expression was found to positively correlate to TGF-βRII expression and negatively correlate to TGF-βRI expression in PDA cell lines. We hypothesized that MUC1 overexpression induces TGF-β mediated non-canonical signaling pathways which is known to be associated with poor prognosis. In this study, we report that MUC1 overexpression in PDA cells directly activates the JNK pathway in response to TGF-β, and leads to increased cell viability via up-regulation and stabilization of c-Myc. Conversely, in low MUC1 expressing PDA cells, TGF-β preserves its tumor-suppressive function and inhibits phosphorylation of JNK and stabilization of c-Myc. Knockdown of MUC1 in PDA cells also results in decreased phosphorylation of JNK and c-Myc in response to TGF-β treatment. Taken together, the results indicate that overexpression of MUC1 plays a significant role in switching the TGF-β function from a tumor-suppressor to a tumor promoter by directly activating JNK. Lastly, we report that high-MUC1 PDA tumors respond to TGF-β neutralizing antibody in vivo showing significantly reduced tumor growth while low-MUC1 tumors do not respond to TGF-β neutralizing antibody further confirming our hypothesis.